Exploration of Mathematical Concepts on Interpretation the Principal of Ukhuwah Islamiyah through Autoethnographic Study - Amrul Huda Fathir; Neni Mariana; Naif Mastoor Alsulami (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractMathematics is a fundamental science that extends beyond the classroom and plays a crucial role in daily life, including within religious contexts, like the principle of Ukhuwah Islamiyah in Islam. Divergent perspectives often overlook this principle, which aims to unite Muslims, thereby impacting children's understanding of diversity. This study explores how mathematical concepts can be interpreted through the lens of Ukhuwah Islamiyah to reinforce both the principle and mathematical thinking. Using a qualitative method with an autoethnographic approach, the researcher (first author) reflects on personal experiences related to Qur'anic and Hadith teachings. Data were collected through narrative writing, narrative inquiry, document analysis, and expert interviews and validated using trustworthiness and authenticity criteria. The findings highlight various mathematical concepts linked to Ukhuwah Islamiyah, such as numbers and operations, geometry (lines and angles), building nets, and the alignment of lines and angles in congregational prayer. These insights provide a basis for integrating Islamic values into elementary mathematics education, fostering meaningful learning experiences. In conclusion, these mathematical elements provide valuable opportunities for classroom instruction, promoting character development, enhancing mathematical reasoning, and reinforcing the principle of Ukhuwah Islamiyah. Keywords: mathematics education, Islamic teachings, ukhuwah islamiyah.AbstrakMatematika adalah ilmu fundamental yang melampaui ruang kelas dan memainkan peran penting dalam kehidupan sehari-hari, termasuk dalam konteks keagamaan, seperti prinsip Ukhuwah Islamiyah dalam Islam. Perspektif yang berbeda sering mengabaikan prinsip ini, yang bertujuan untuk menyatukan umat Muslim, sehingga memengaruhi pemahaman anak-anak tentang keragaman. Studi ini mengeksplorasi bagaimana konsep matematika dapat diinterpretasikan melalui lensa Ukhuwah Islamiyah untuk memperkuat prinsip dan pemikiran matematis. Dengan menggunakan metode kualitatif dengan pendekatan autoetnografi, peneliti (penulis pertama) merefleksikan pengalaman pribadi yang berkaitan dengan ajaran Al-Qur'an dan Hadits. Data dikumpulkan melalui penulisan naratif, penyelidikan naratif, analisis dokumen, dan wawancara ahli, serta divalidasi menggunakan kriteria kepercayaan dan keaslian. Temuan menyoroti berbagai konsep matematika yang terkait dengan Ukhuwah Islamiyah, seperti angka dan operasi, geometri (garis dan sudut), membangun jaring, dan penyelarasan garis dan sudut dalam salat berjamaah. Wawasan ini memberikan dasar untuk mengintegrasikan nilai-nilai Islam ke dalam pendidikan matematika dasar, sehingga mendorong pengalaman belajar yang bermakna. Kesimpulannya, unsur-unsur matematika ini memberikan peluang berharga untuk pengajaran di kelas, mendorong pengembangan karakter, meningkatkan penalaran matematika, dan memperkuat prinsip Ukhuwah Islamiyah.Kata kunci: pendidikan matematika, ajaran Islam, ukhuwah islamiyah.